Foreign direct investment, domestic investment, and the role of institutions in Central, Eastern, and South-Eastern Europe - Bucevska Vesna; Merdzan Gunter (Ekonomski Anali)
The paper examines the relationship between foreign direct investment (FDI) and domestic investment in Central, Eastern, and South-Eastern European (CESEE) countries from 1995 to 2021. The primary hypothesis posits that FDI exerts a positive influence on domestic investment, with variations observed across diverse institutional contexts. The research utilises fixed effects and a one-step difference generalised method of moments (GMM) to determine whether FDI leads to an increase or decrease in domestic investment in CESEE countries. The findings indicate that FDI has a favourable and statistically significant influence on domestic investment. However, the coefficients for FDI are less than one, indicating that while FDI stimulates overall investment, it does not create a crowding-in effect where the rise in total investment surpasses the FDI inflows. When the data is split on the basis of institutional quality, it is evident that FDI continues to positively impact domestic investment in high and low-institutional- quality settings. The coefficients for FDI in both subgroups are less than one, implying that institutional quality does not substantially change the correlation between FDI and domestic investment. These results indicate the positive and significant impact of FDI on domestic investment, without crowding-in effects for the entire sample of CESEE economies and both subgroups that differ in institutional quality.